Allocation of security cost in a pure pool-based electricity market design base on load contribution towards security problem - Noor Zarith Iffah Jasmani, 1983-; Md. Pauzi Abdullah; Fakulti Kejuruteraan Elektrik (2009)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2009